Effects of disturbance and altitude on soil seed banks of tropical montane forests. (8th November 2013) - Lippok, Denis; Walter, Florian; Hensen, Isabell; Beck, Stephan G.; Schleuning, Matthias
Abstract: Vast areas of tropical forests have been deforested by human activities, resulting in landscapes comprising forest fragments in matrices of deforested habitats. Soil seed banks (SSB) are essential sources for the regeneration of tropical forests after disturbance. In a fragmented montane landscape in the Bolivian Andes, we investigated SSB in three different habitat types that were associated with different degrees of disturbance, i.e. in forest interior, at forest edges and in deforested habitats. Sampling of habitats was replicated at six sites ranging in altitude from 1950 to 2450 m asl. We extracted seeds from dried soil samples by sieving, classified seeds into morphospecies and size classes, and characterized SSB in terms of density, species richness and composition. We tested effects of disturbance (i.e. habitat type) and altitude on SSB characteristics. Overall, small seeds (<1 mm) dominated SSB (81% of sampled seeds). Seed density and species richness were lowest in deforested habitats, especially in large seeds and distant from adjacent forests (≥20 m), while small-seeded species were most numerous near forest margins. Species turnover between habitats was high. Altitude altered the composition of SSB, but had no effects on seed density and species richness. We conclude that the potential of SSB for natural regeneration of deforested habitats is low and decreases with increasing distance from forest remnants and that forest edges may be eventually invaded by small-seeded species from deforested habitats.